Employee Work Productivity is Assessed in Terms of Integrity, Competence, Workload, and Use of Information Technology - Suharno Suharno; Sudarwati Sudarwati; Istiatin Istiatin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to examine and analyze the influence of integrity, competence, workload, and information technology on the work productivity of employees at the Bapenda Office of Surakarta City. The study was conducted at the Bapenda Office of Surakarta City. The research sample consisted of 58 TKPK employees working at Bapenda Surakarta City, using a census sampling technique. Data were collected using questionnaires. Data analysis was conducted using multiple linear regression analysis. The results of this study indicate that integrity has a significant effect on the work productivity of employees at the Bapenda Office of Surakarta City. Competence has a significant effect on the work productivity of employees at the Bapenda Office of Surakarta City. Workload has a significant effect on the work productivity of employees at the Bapenda Office of Surakarta City. The utilization of information technology has a significant effect on the work productivity of employees at the Bapenda Office of Surakarta City. Integrity, competence, workload, and The utilization of information technology has a simultaneous and significant effect on the work productivity of employees at the Bapenda Office of Surakarta City.